Performance analysis on spectrum coexistennce between wi-fi networks and ground based radar using database assisted spectrum sensing scheme - Mohamoud, Mohamoud Ali; Elsheikh, Elsheikh Mohamed Ahmed; Habaebi, Mohamed Hadi (IEEE, 2016)
Cognitive Radio (CR) is an intelligent scheme for opportunistic access of idle resources and a solution for spectrum resources scarcity. In this article a new technique for spectrum access is proposed. This technique combines spectrum sensing with geolocation database. The aim of the hybrid system is to take advantage of temporal spectrum opportunity resulting from RADAR rotation. To assess scheme performance, primary systems protection distance and resultant secondary Wi-Fi network is analyzed. It is found that when blind sensing without any information about RADAR rotation and antenna pattern is employed the primary protection distance is very large, also the Wi-Fi network can achieve required throughput only when it is located beyond the protection region. On the other hand, when information about RADAR rotation and antenna pattern is provided through database, the secondary devices can coexist with RADAR and the protection distance will be minimal. The proposed technique can be employed in RADAR bands in the range of 960-1400 MHz, 2.7-3.6 GHz and 5-5.85 GHz. These bands occupy quite large bandwidth and have very low utilization. It is expected to pose a solution for the static nature of geolocation database method. It minimizes the interference caused by secondary users by improving the probability of detection.